Adverse effects under immune checkpoint inhibitors on (18F)FDG PET/CT imaging - Sachpekidis, Christos; Hassel, Jessica C.; Dimitrakopoulou-Strauss, Antonia (The quarterly journal of nuclear medicine and molecular imaging)
Despite their undisputed contribution to the management of various tumors and the prolongation of patient survival, immune checkpoint inhibitors (ICIs) exert their effect at the cost of toxicity. In the context of the activation of the host immune system triggered by ICIs, collateral, inflammatory side effects, commonly addressed as immune-related adverse events (irAEs) often occur. Early detection of irAEs can be critical for adequate decisions on patient management that may subsequently improve patient outcome. Moreover, the emergence of irAEs has been linked with the antitumor effect elicited by ICIs, thus, their identification may potentially provide prognostic information. Although the diagnosis of irAEs is mainly clinical, some adverse events may be asymptomatic and only diagnosed by imaging modalities. At the same time, radiological signs of irAEs are not necessarily associated with clinical symptoms, however, clinicians should be alerted to their presence. Among imaging modalities [18F]FDG PET/CT has shown satisfying efficiency in response assessment and monitoring of ICIs' treatment, especially in patients suffering from metastatic melanoma and lung cancer. In this context, [18F]FDG PET/CT may also be a valuable method for surveillance of irAEs during immunotherapy. This article aims to review the most common adverse events observed on [18F]FDG PET/CT under immunotherapy and summarize potential results linking PET signs of irAEs with response assessment to ICIs.